Dimensions and reliability of a hospital safety climate questionnaire in Chinese health‐care practice. Issue 2 (12th April 2013) - Smith, Derek R; Zhao, Isabella; Wang, Lina; Ho, Alan
Abstract : The aim of the current study was to examine the dimensions and reliability of a hospital safety climate questionnaire in Chinese health‐care practice. To achieve this, a cross‐sectional survey of health‐care professionals was undertaken at a university teaching hospital in Shandong province, China. Our survey instrument demonstrated very high internal consistency, comparing well with previous research in this field conducted in other countries. Factor analysis highlighted four key dimensions of safety climate, which centred on employee personal protection, employee interactions, safety‐related housekeeping and time pressures. Overall, this study suggests that hospital safety climate represents an important aspect of health‐care practice in contemporary China.